A psicologia e o campo da educação inclusiva: uma compreensão fenomenológica-hermenêutica de experiências formativas - Silva, Lia Spadini da (2022)
The inclusion of people with disabilities has been constantly debated and studied. Faced with claims for the exercise of the right of these people to be in school environments, there is a need to understand in a more accurate and detailed way these schooling processes and their relationship with health professionals, among them, psychologists. In 2018, a review of the national curriculum guidelines for Psychology graduation courses was carried out, which has invited the professional category to review its training base. Thus, considering this scenario, this thesis, based on the phenomenological-hermeneutic method, aims to investigate how psychologists are trained in the field of Inclusive Education. To do it, analysis was performed over the syllabus of three universities located in the city of São Paulo, based on the criteria of online availability. Then, reflective interviews were carried out with three psychologists graduated by these same institutions who were working in the field of Inclusive Education. At the end of this investigation, it was possible to perceive that, although there are disciplines in the Universities that discuss the theme of Inclusive Education for people with disabilities, in the participants' view there is a gap in the formation of graduations and there is a perception that the subject should be more present during the course and linked to concrete intervention experiences. It has also been concluded that dealing with the graduation of Psychology professionals consists on raising a discussion on how knowledge is reachable through experience